دور التعليم الإلكتروني في تنمية مهارات البحث العلمي لدى طلبة برامج الدراسات العليا في الجامعات الفلسطينية - عودة، فراس محمد عبد (الجامعة الاسلامية بغزة, 2013)
هدفت الدراسة إلى معرفة دور التعليم الإلكتروني في دعم عملية البحث العلمي لخدمة العملية التعليمية من خلال تنمية مهارات البحث العلمي لدى طلبة كليات التربية في برامج الدراسات العليا في الجامعات الفلسطينية، وتعد تقنيات التعليم الإلكتروني مطلبًا أساسًا في عصرنا الحالي، فقد أسهمت في رفع المستوى المعرفي والعلمي لدى المتعلمين، واقتحمت العديد من المجالات التعليمية بفضل المعلومات التي توفرها للباحثين والطلاب والمعلمين وغيرهم. ولتحقيق أهداف الدراسة قام الباحث باستخدام المنهج الوصفي التحليلي الذي يحاول من خلاله وصف الظاهرة موضوع الدراسة، وتمثل مجتمع الدراسة في طلبة كلية أصول التربية ضمن برامج الدراسات العليا في الجامعات الفلسطينية (الجامعة الإسلامية، جامعة الأزهر)، وقد شملت عينة الدراسة (40) طالباً وطالبة للعام الدراسي 2012/2013، وقام الباحث ببناء استبانة مكونة من (3) أبعاد و(38) فقرة، لجمع البيانات الخاصة بالدراسة. وتشير نتائج الدراسة إلى: 1. درجة تقبل عالية لطلبة كلية التربية ضمن برامج الدراسات العليا للتعليم الإلكتروني، والاستفادة من تطبيقاته في تنمية مهاراتهم في البحث العلمي. 2. نجاح تطبيقات التعليم الإلكتروني في تنمية مهارات البحث العلمي لدى طلبة برامج الدراسات العليا في الجامعات الفلسطينية من خلال تطوير مهارات استخدام قواعد المعلومات، ومهارات استخدام الإنترنت في البحث العلمي. 3. عدم وجود فروق ذات دلالة إحصائية في دور التعليم الإلكتروني في تنمية مهارات البحث العلمي لدى طلبة برامج الدراسات العليا في الجامعات الفلسطينية تعزى لمتغير الجنس (ذكور، إناث) 4. عدم وجود فروق ذات دلالة إحصائية في دور التعليم الإلكتروني في تنمية مهارات البحث العلمي لدى طلبة برامج الدراسات العليا في الجامعات الفلسطينية تعزى لمتغير الجامعة (الإسلامية، الأزهر) ومن أهم توصيات الدراسة: 1. تحديث مقررات تكنولوجيا التعليم لطلبة برامج الدراسات العليا في كليات التربية في ضوء مستحدثات تكنولوجيا التعليم وفى ضوء الثورة التكنولوجية المعاصرة 2. العمل على تجهيز مختبرات خاصة بطلبة الدراسات العليا في كليات التربية في الجامعات الفلسطينية لاستخدام تقنيات التعليم الإلكترونية والاستفادة منها في حياتهم الأكاديمية 3. تشجيع طلبة برامج الدراسات العليا المتميزين في مجال الاستفادة من تقنيات التعليم الإلكتروني معنوياً ومادياً، من أجل تعزيز قضايا البحث العلمي، والمعلوماتي، بتوظيف تقنيات التعليم الإلكتروني في خدمة المادة الدراسية وتطويرها. 4. ضرورة العمل على رفع المستوى التقني لدى طلبة كلية التربية ضمن برامج الدراسات العليا في التعرف على الإمكانات التي تقدمها بيئة التعلم الإلكتروني لسد الفجوة الإلكترونية من خلال طرح مقررات الكترونية تصقل مهاراتهم العملية وتنميها. The study aimed to find out the role of e-learning in supporting the process of scientific research to serve the educational process through the development of research skills among the students of colleges of education in graduate programs at Palestinian universities, and is the technology of e-learning demand mainly in the present era, it has contributed to raising the level of knowledge and scientific learners, and stormed several educational areas thanks to information provided by the researchers, students, teachers and others. To achieve objectives of the study, the researcher using descriptive analytical method that tries which describe the phenomenon under study, and represent the community of study in the students of the Faculty of Education within the graduate programs at universities (Islamic University, Al-Azhar University), The study sample included (40) students for the academic year 2012/2013, and researcher has built a questionnaire consisting of (3) and dimensions (38) items, to collect data for the study. The results of the study indicate: 1) High degree accept students of the Faculty of Education within graduate programs for e-learning, and take advantage of its applications in the development of skills in scientific research. 2) The success of e-learning applications in the development of scientific research skills of students in graduate programs at Palestinian universities through the development of skills to use databases, and Internet skills in scientific research. 3) There is no statistically significant differences in the role of e-learning in the development of scientific research skills among the students of graduate programs in the Palestinian universities due to the variable sex (male, female) 4) There is no statistically significant differences in the role of e-learning in the development of scientific research skills among the students of graduate programs in the Palestinian universities attributed to the university (the Islamic Al-Azhar) One of the main recommendations of the study: 1) Reload decisions technology education for students of graduate programs in the colleges of education in the light of educational technology innovations and in the light of contemporary technological revolution 2) Work to prepare the private laboratories with students graduate in the colleges of education in the Palestinian universities to use e-learning technologies and take advantage of them in their academic life 3) Encourage students outstanding graduate programs in the area to take advantage of e-learning techniques morally and materially, in order to promote scientific research issues, and information, employing e-learning technologies in the service of the subject and developed. 4) The need to work to raise the technical level of the students of the Faculty of Education within graduate programs to identify potential offered by e-learning environment to bridge the gap by introducing electronic auction decisions refine their skills and develop process.
Keywords: البحث العلمي -- التعليم الإلكتروني -- برامج الدراسات العليا -- الجامعات الفلسطينية